Characterisation of tetraspanins from Schistosoma haematobium and evaluation of their potential as novel diagnostic markers. - Gebeyaw G Mekonnen; Bemnet A Tedla; Mark S Pearson; Luke Becker; Matt Field; Abena S Amoah; Govert van Dam; Paul L A M Corstjens; Takafira Mduluza; Francisca Mutapi; Alex Loukas; Javier Sotillo (Public Library of Science (PLoS), 2022)
Schistosoma haematobium is the leading cause of urogenital schistosomiasis and it is recognised as a class 1 carcinogen due to the robust association of infection with bladder cancer. In schistosomes, tetraspanins (TSPs) are abundantly present in different parasite proteomes and could be potential diagnostic candidates due to their accessibility to the host immune system. The large extracellular loops of six TSPs from the secretome (including the soluble excretory/secretory products, tegument and extracellular vesicles) of S. haematobium (Sh-TSP-2, Sh-TSP-4, Sh-TSP-5, Sh-TSP-6, Sh-TSP-18 and Sh-TSP-23) were expressed in a bacterial expression system and polyclonal antibodies were raised to the recombinant proteins to confirm the anatomical sites of expression within the parasite. Sh-TSP-2, and Sh-TSP-18 were identified on the tegument, whereas Sh-TSP-4, Sh-TSP-5, Sh-TSP-6 and Sh-TSP-23 were identified both on the tegument and internal tissues of adult parasites. The mRNAs encoding these TSPs were differentially expressed throughout all schistosome developmental stages tested. The potential diagnostic value of three of these Sh-TSPs was assessed using the urine of individuals (stratified by infection intensity) from an endemic area of Zimbabwe. The three Sh-TSPs were the targets of urine IgG responses in all cohorts, including individuals with very low levels of infection (those positive for circulating anodic antigen but negative for eggs by microscopy). This study provides new antigen candidates to immunologically diagnose S. haematobium infection, and the work presented here provides compelling evidence for the use of a biomarker signature to enhance the diagnostic capability of these tetraspanins.